Diagnostic and Assessment Benefits and Barriers of BIM in Construction Project Management - Faiq Al-Zwainy; Ibraheem A. Mohammed; Kamil A. K. Al-Shaikhli (Salehan Institute of Higher Education, 2017)
This paper aims to diagnostic and assessment the benefits and barriers of Building Information Modelling in the construction project management. Both open and closed questionnaire was used to explore the views of a number of Iraqi engineers; in order to investigate the level of BIM implementation in Iraq construction sector. Questionnaire indicated an acceptable awareness of (BIM) in Iraq, especially among the young generation of engineers which indicates the arrival of the evolutionary stream of BIM in the next few years. Moreover, questionnaire showed that the most important advantage of implementing BIM in the Iraqi construction sector was the ability to generate accurate 2D plans at any stage, while the least important advantage was the ability to provide a careful planning of the site facilities, with a relative importance of (82 %) and (33 %) respectively. Furthermore, the most important barrier to its implementation was the unspecified responsibilities for data content, as presented by questionnaire, while the least important barrier was the lack of programs efficiency in data exchange and internal collaboration, with a relative importance of (81 %) and (34 %) respectively.